Photocatalytic heterostructures-based BiFeO3 embedded liquid natural rubber (LNR) for highly removal of cationic dye under direct sunlight - Ridzuan, Nur Diyan Mohd; Kaus, Noor Haida Mohd; Lazim, Mohd Azwani Shah Md; Kobayashi, Takaomi; Adnan, Rohana; Othman, Muhammad Zamir; Kassim, Mohamad Haafiz Mohamad (Elsevier Sci Ltd, 2024)
Indexed by WOS/SCOPUS/ERA